Advances in Prefabricated Concrete Technology for Modern Infrastructure - Fenti Niatman Zega; Michael Macarona (Momentum International Journal of Civil Engineering (MIJCE), 2025)
The demand for rapid, cost-effective, and sustainable infrastructure solutions has driven significant advancements in prefabricated concrete technology over the past decade. This study explores recent innovations in the design, production, and implementation of prefabricated concrete components within modern infrastructure projects, including bridges, buildings, and transportation systems. Emphasis is placed on modular construction techniques, high-performance materials, digital fabrication methods, and connection systems that enhance structural efficiency, durability, and construction speed. Case studies from urban infrastructure developments illustrate how prefabrication reduces construction time, minimizes on-site labor, improves quality control, and decreases environmental impact through material optimization and waste reduction. Furthermore, the integration of Building Information Modeling (BIM) and automation in precast fabrication facilities has streamlined the design-to-production workflow, enabling greater precision and customization. The paper concludes that prefabricated concrete technology plays a pivotal role in addressing the growing infrastructure needs of rapidly urbanizing societies while supporting the global transition toward more sustainable construction practices.